Determination of lanthanide and actinide elements by energy dispersive x-ray fluorescence spectrometry applying DLLME preconcentration and dried spot - Sá, Ívero P.; Almeida, Ohana N.; Lima, Daniel De C.; da Silva, Erik G.P.; Santos, Luana N.; Luzardo, Francisco H.M.; Velasco, Fermin G.; Gonzalez, Mário H. [UNESP]; Amorim, Fábio A.C. (Elsevier, 2021)
This work describes an analytical procedure to determination of trace amount of lanthanide and actinide chemistry elements (LAEs) in water samples by energy dispersive x-ray fluorescence spectrometry (EDXRF) with the prepare of the samples using simultaneous preconcentration procedure based on the dispersive liquid-liquid microextraction (DLLME). Critical study of the analytical procedure occurred the following way: ions of Eu, Er, Ho, Th, U and Yb presents in 5.0 mL of aqueous sample have been complexed with 2-(5-bromo-2-pyridylazo)-5-(diethylamino)-phenol (Br-PADAP) in a mixture contained solvents (disperser and extractant). After centrifugation, 30 μL of the sedimented organic phase has been removed and deposited on membrane disk and submitted to EDXRF analysis. The optimization step was performed by: i) screening factor with mixture design for the disperser solvent (acetone, acetonitrile and ethanol) and extractant solvent (carbon tetrachloride, trichlorethylene and 1,2-dichloroethane); ii) Box-Behnken design for the independents variables: pH, Br-PADAP concentration, volume of disperser solvent and volume of extractant solvent. The optimized conditions were: 500 μL of disperser solvent (ethanol), 60 μL extractant solvent (carbon tetrachloride and trichlorethylene, 1: 1 ratio), Br-PADAP 1.8 × 10−5 mol L−1 and pH 8.0. In these conditions, the procedure allows the determination of Eu, Ho, Er, Yb, Th and U with quantification limits of 10.5; 8.6; 4.3; 7.0; 6.6 and 1.1 μg L−1, respectively; preconcentration factor between 18 and 74, and precision (RSD%) below that 6%. Salting out effect, presence of other ions, and additions/recoveries of analytes in real samples was verified and the recovery values were between of 90 to 107%. Analytical method has been applied in waters samples and groundwater from uranium mining region.
Keywords: Actinides; Dried spot; Lanthanides; Liquid phase microextraction; Multivariate optimization; Water analysis; X-ray fluorescence spectrometry